2018
DOI: 10.1161/hypertensionaha.118.11060
|View full text |Cite
|
Sign up to set email alerts
|

FGF23 (Fibroblast Growth Factor-23) and Incident Hypertension in Young and Middle-Aged Adults

Abstract: Blacks have the highest prevalence of hypertension in the United States. Higher levels of FGF23 (fibroblast growth factor-23) have been associated with worse cardiovascular outcomes. Whether FGF23 is associated with rising blood pressure (BP) and racial differences in incident hypertension is unclear. We studied 1758 adults (45.0±3.7 years; 57.8% female; 36.9% black) without hypertension or cardiovascular disease who participated in the year 20 (2005-2006) follow-up examination of the CARDIA study (Coronary Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…Accordingly, FGF23 levels are increased in the frontal lobe of CKD patients (Marebwa et al, 2018), where FGF23 is shown to act directly on hippocampal neurons of CKD patients (Haffner and Leifheit-Nestler, 2017). A previous study showed that higher serum levels of FGF23 were independently associated with increased BP (Akhabue et al, 2018). Based on the aforementioned studies, we believe that the increased levels of FGF23 in the CSF of patients with CKD could stimulate RVLM and thus sympathetic nerve activity leading to hypertension in those patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, FGF23 levels are increased in the frontal lobe of CKD patients (Marebwa et al, 2018), where FGF23 is shown to act directly on hippocampal neurons of CKD patients (Haffner and Leifheit-Nestler, 2017). A previous study showed that higher serum levels of FGF23 were independently associated with increased BP (Akhabue et al, 2018). Based on the aforementioned studies, we believe that the increased levels of FGF23 in the CSF of patients with CKD could stimulate RVLM and thus sympathetic nerve activity leading to hypertension in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…Klotho is also known to be a component of the FGF23 receptor (FGFR1) (Erben, 2017). FGF23 (251 amino acids; molecular weight, 32 kDa), mainly produced by osteocytes and osteoblasts, is related to the elimination of serum phosphate in the kidneys (Bech et al, 2015) and is reported to cause myocardial hypertrophy, atherosclerosis, and hypertension (Akhabue et al, 2018). Moreover, a previous study shows that the high serum FGF23 levels cause hypertension in patients with CKD (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Whether the associations of FGF23 levels with LVH in patients of all ages with [ 6–8 ] or without known CKD [ 46 , 47 ] are mediated through predominantly direct effects of FGF23 on the myocardium independent of hypertension [ 9 ] and renal impairment [ 12 ], or indirectly through BP changes, remains debatable. Most studies reported weak or no independent associations between FGF23 and BP [ 11 ] although recently higher FGF23 levels were independently associated with incident hypertension in younger adults without CKD [ 48 ]. We did not elicit significant associations between FGF23 levels and either systolic or diastolic BP measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of FGF 23 levels in the pre-and post-kidney transplant period to BP level or development of HTN after kidney transplantation is unknown. However, given that a higher level of FGF23 is associated with increased SBP and DBP as well as an incident HTN in 1,758 non-hypertensive young adults without CKD or CVD (114), this association may hold true for the transplant population. Despite this, further studies are necessary.…”
Section: Fibroblast Growth Factor (Fgf) 23mentioning
confidence: 99%